The Impact Of Learning Style And Self – Efficacy On Academic Performance Of Mba Candidates - A. H. Rashid, Abeer (2004)
The demand for the MBA program is considered high in Malaysia and to select the suitable MBA candidate that can excel in his performance encouraged me to do this research. The MBA program is different from other postgraduate program in the sense that it’s candidates merge from different backgrounds with different learning styles and this might make them differ in their academic performance.